Developing a Pedagogical Model Integrating E-Learning, PAD Class, and Project-Based Learning for Innovation and Entrepreneurship Education Aligned with the Sustainable Development Goals (SDGs) - Kun Liu; Jiraporn Chano; Yannapat Seehamongkon (ASEAN Journal of Educational Research and Technology, 2026)
This study aimed to develop a pedagogical model for innovation and entrepreneurship education that enhances students’ creativity and attitudes, in alignment with Sustainable Development Goal 4 on quality education. The model (referred to as the E-Learning- Presentation-Assimilation-Discussion-Project-Based (EPP) Model) combines online learning, structured classroom interaction, and experiential projects. Grounded in Constructivism Theory, Educational Ecology Theory, and the Theory of Inventive Problem Solving (TRIZ), 9the model was developed using expert validation and implemented in a classroom setting. Students showed notable gains in creativity and learning attitudes after the intervention. These outcomes occurred because the model fosters active engagement, collaborative exploration, and reflective application. The impact of this integrated instructional design offers practical guidance for advancing student-centered, sustainable entrepreneurship education in higher learning institutions